TRAFFIC PLANNING IN KUNINGAN CITY CENTER - Pratama, Diky Irdianto Pratama; Anwar, Saihul (Journal of Green Science and Technology, 2017)
This research was conducted to improve the performance of service of Siliwangi Road which decreased. The data obtained from the Department of Transportation brass form LHR data brass city, road length, and the average speed of the vehicle, Then in if the degree of saturation of the Road in order to know the success of the New Planning. To facilitate the research and also because it has different problems Siliwangi road for 2 parts cut off by crossing, Siliwangi Street 1 which starts from Cijoho roundabout Until the intersection near Smpn 1 Kuningan has LHR 2563 smp with degree of saturation 0,97 at level Service E and Jalan Siliwangi 2 starting from intersection of Smpn 1 Kuningan Until the junction of Jalan Veteran has LHR 1761 smp with degree of saturation 0,67 level of service C. After in doing traffic engineering level of road service go up, Siliwangi Street 1 become C with degree of saturation 0.57 also Jalan Siliwangi 2 level service C with degree of saturation 0,51.